Man in the Modern Age (Routledge Revivals). - Jaspers, Karl (Routledge revivals., 2014)
First published in English in 1933, this detailed philosophical examination of the contemporary state and nature of mankind is a seminal work by influential German philosopher Karl Jaspers. Elucidating his theories on a variety of topics pertaining to contemporary and future human existence, Man in the Modern Age is an ambitious and wide-ranging work, which meditates upon such diverse subjects as the tension between mass-order and individual human life, our present conception of human life and the potential for mankind's future existence. Written shortly before the accession to pow.